1973
DOI: 10.3382/ps.0521637
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Chick Edema Disease

Abstract: Based on recently obtained analytical information, calculations were made to ascertain the toxic effects of chick edema factor (CEF) preparations for the intact day-old chick, the developing chick embryo, and the monkey. Results indicate that CEF, principally polychlorodibenzo-^>-dioxins, elicits toxic responses in these experimental animals. For the intact chick, approximately 9 jug./chick of total dioxins containing 2-8 chlorine atoms/molecule are detectable. For the fertile chicken egg, less than 1.0 ng. is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…The dioxin-contaminated chicken embryos had brain, leg, and beak malformations and were smaller than uncontaminated embryos. Newly hatched chickens injected with dioxins as embryos were smaller than controls and had sparse and defective down formation (Flick et al, 1965(Flick et al, ,1973. The pathological changes we saw, particularly the slight growth depression, edema, and sparse down follicles, are consistent with the effects of dioxins seen in Flick's studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The dioxin-contaminated chicken embryos had brain, leg, and beak malformations and were smaller than uncontaminated embryos. Newly hatched chickens injected with dioxins as embryos were smaller than controls and had sparse and defective down formation (Flick et al, 1965(Flick et al, ,1973. The pathological changes we saw, particularly the slight growth depression, edema, and sparse down follicles, are consistent with the effects of dioxins seen in Flick's studies.…”
Section: Discussionsupporting
confidence: 84%
“…The edema was consistent with literature descriptions of chick edema disease (Sanger et al, 1958;Schmittle et al, 1958), the causative factor being identified as PCDDs (Flick et al, 1973). Three-day-old chickens treated with 1 or 10 ng TCDD/kg/d (i.e., about 50 ng/chick/d) for 3 wk suffered subcutaneous and pulmonary edema, distended abdomens, and increased peritoneal and pericardial fluid (Schwetz et al, 1973).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although most of the PCDD and PCDF homologues in eggs were negatively correlated with reproductive variables, TCDD-EQs provided the highest correlations. Thus, reproductive failure in our study probably resulted from cumulative effects rather than from a single compound, as suggested in other studies (7,12,20,21). …”
Section: Methodssupporting
confidence: 58%
“…A method was recently developed for the detection of low concentrations of TeDD in biological tissue,12 but an attempt to use this method in a monitoring program of the Environmental Protection Agency was not successfuL 15 Published information on the bioaccumulation of TCDD after long-term exposure is not available. Flick et al 16 found that the feeding of toxic fat contaminated with chlorinated dibenzodioxins resulted in pronounced cumulative toxicity in monkeys. Studies with single oral doses of C 14 -labeled 2,3,7 ,8-TCDD in rats indicate that half of the radioactive material was recovered within 21 days in the feces and only 13% in urine and 3% in expired air.…”
Section: Discussionmentioning
confidence: 98%